Norway : Financial Sector Assessment Program-Technical Note-Linkages and Interconnectedness in the Norwegian Financial System. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note reviews linkages and interconnectedness in the Norwegian financial system for Norway. Norway's banks have important connections with global financial centers, but regional links are also important. Norwegian banks are very dependent on global financial centers as sources of funding and to hedge currency risks. Cross-sectoral exposures of Norway's banks, insurance companies, and real estate companies are significant and extend beyond the Nordic region. The authorities are encouraged to expand their current monitoring efforts of crossborder and cross-sectoral exposures of the Norwegian financial sector, and to conduct regional stress tests. For this effect, the authorities can resort to market data and, if available, to balance sheet data of exposures at the individual financial institution level.